Disproportionality analysis of adverse events associated with ipilimumab and nivolumab combination therapy based on FAERS database - Xianyu Dai; Hongliang Cao; Jiajun Li; Tao Zhang; Yuchuan Hou (Scientific Reports)
Abstract The combination of immune checkpoint inhibitors (ICIs), such as ipilimumab and nivolumab, has revolutionized cancer treatment, particularly for advanced melanoma and other solid tumors. However, rare adverse events (AEs) associated with this combination are often underreported in clinical trials. This study aimed to investigate the safety profile of these drugs using the FDA Adverse Event Reporting System (FAERS) database. A retrospective analysis of data from 2015 to the first quarter of 2024 was conducted, focusing on AEs submitted by healthcare professionals. Disproportionality analysis, using algorithms like Reporting Odds Ratio (ROR) and Bayesian Confidence Propagation Neural Network (BCPNN), identified AE signals. A total of 19,462 reports related to the combination therapy were retrieved, spanning 20 System Organ Classes (SOCs), with endocrine and hepatobiliary disorders being most affected. Additionally, 125 unexpected significant AEs were identified, including thyrotoxic crisis, diabetes insipidus, immune-mediated optic neuritis, cystitis, eyelid ptosis, complete atrioventricular block, etc. The highest frequency of AEs occurred within the first 30 days of treatment (38.1%), with a decrease in incidence over time, as indicated by the Weibull Shape Parameter (WSP) test. These findings highlight the importance of continuous monitoring of ICIs in clinical practice.